'Like a rug had been pulled from under you': The impact of COVID‐19 on teachers in England during the first six weeks of the UK lockdown. (25th September 2020) - Kim, Lisa E.; Asbury, Kathryn
Abstract : Background: On 20 March 2020, in response to COVID‐19, UK schools were closed to most pupils. Teachers were required to put remote teaching and learning in place with only two days' notice from the government. Aims: The current study explores teachers' experiences of this abrupt change to their working practices, and during the 5–6 weeks that followed. Sample: Twenty‐four teachers from English state schools were interviewed, representing mainstream primary and secondary schools and a range of years of experience and seniority. Methods: Participants were asked to tell stories of three key scenes during the first 5–6 weeks of lockdown: a low point, a high point, and a turning point. A reflexive thematic analysis of their narratives was conducted. Results and Conclusions: Six themes were identified: uncertainty, finding a way, worry for the vulnerable, importance of relationships, teacher identity, and reflections . Teachers' narratives suggest that, after an initial period of uncertainty they settled into the situation and found a way forward, supported by strong relationships. However, they remain extremely worried about the most vulnerable pupils and want more joined‐up thinking from the government on how to support them effectively, along with clarity from policymakers to enable planning ahead. Teachers reflected on how to use their learning during this period to improve pupils' experiences of education post‐COVID‐19, and on how aspects of shared teacher identity have worked as stressors and coping mechanisms. These initial interviews form the baseline for a longitudinal interview study of teachers' experiences of COVID‐19 in England.